Malay and Cebuano ditransitives: A minimalist perspective - Jubilado, Rodney C.; Manueli, Maria Kristina S. (Journal of Modern Languages, 2017)
In the tradition of the generative school of thought in linguistics, the Universal Grammar (UG) is in the forefront in shifting linguistics from behavioral to cognitive science making linguistics an integral part of the study of cognition (Bocckx 2008:6-9). The study of linguistic theory focuses on the knowledge of language and the acquisition thereof. Hence, language theory becomes inseparable from the theory of language acquisition. With linguistlc competence that a native speaker (NS) possesses, the tacit knowledge embedded in the cognitive system of the NS is necessary to be studied for the characterization and the discovery of the linguistic properties within the premises of UG. The study of the internalized linguistic system of NS bears obvious implications in the description and analysis of a particular linguistic system. By usingthe Minimalist Program, this paper deals with the linguistic analysis on the Cebllano and Malay languages in particular the computation towards Logical Form - the narrow syntax (Chomsky 2004:4). This paper attempts to analyze the predicate and the temporal layers of the clause structures of the said languages. The focused clause structures herein are those of the ditransitives. Ditransitives, often called triadic verbs, are a type of predicate with three arguments in its argument/thematic structure. Sentential constructions involving ditransitive or triadic verbs have two internal arguments and one external argument. The basic notion here is that dltransitives are a type of transitive verbs w ith two objects, traditionally known as direct object and indirect object, in the domain of the VP structure. In the study of ditransitives, there is a need to delve more into the syntactic and semantic properties of this particular predicate type concerning computation wherein the arguments and the theta roles arc economically addressed. In particular, the syntactic phenomena are concerned with the case properties of arguments and the conditions associated with the assignment of case. Ditransitives, in Malay and Cebuano, project different cartographies owing to the fact that Cebuano is a predicate-initial language while Malay is subJect-initial ltypologically. The findings of this study will contribute to the current studies on generative linguistics, the Minimalist Program, typology, and Austronesian linguistics.